Analysing Key Responsibilities, Knowledge, and Skill Requirements for HR and Sales Roles: a Case Study of Filco Pvt Ltd - Abhay Javiya; Keval Kantesariya; Jignesh Vidani (International Journal of Global Sustainable Research, 2024)
Human Resource (HR) and Sales functions play a crucial role in organizational success, requiring specialized knowledge, skills, and strategic execution. This study explores the key responsibilities, knowledge domains, and skill sets necessary for HR Executives, Sales Executives, and Sales Representatives within Filco Pvt Ltd. The HR Executive role primarily focuses on recruitment, employee relations, payroll, and compliance, demanding expertise in HR policies, payroll software, and performance management. Sales Executives are responsible for generating new business and maintaining client relationships, requiring strong industry knowledge, CRM proficiency, and market awareness. Meanwhile, Sales Representatives focus on customer management, payment handling, and financial coordination, necessitating strong planning, delivery, and finance handling skills. The study highlights the importance of role-specific competencies in ensuring efficiency and growth in these job functions. While no mandatory certifications are required for these positions, relevant expertise and industry experience remain key to success. The findings provide valuable insights for organizations in structuring job roles effectively, aligning workforce capabilities with business objectives, and enhancing recruitment strategies. This research contributes to human resource and sales management literature by identifying core job elements critical for operational excellence